CHANGING BODIES IN “THE CITY OF PIRATES”: IS A “LAERTE” PEDAGOGY POSSIBLE TO SHAKE COLONIALITIES AND FASCISMS IMPOSED ON GENRES? - Carvalho, Fabiana Aparecida de [UNESP]; Inocêncio, Adalberto Ferdnando (Universidade Federal do Para, 2022)
The present work discusses the animated film “The Pirates City” (2018), directed by Otto Guerra and premiered by the cartoonist Laerte Coutinho, that corporates on screen questions about her transgender process, the adoption of a transvestite identity for herself and about the critic/desconstruction of present masculinities in her works since the decade of 1980. In a succession of layers disposed on a bricolage of comic books, construction of scripts, interviews, protagonists dilemmas and historical contexts of power coloniality, from the individual, from nature, from gender and from knowledge in Brazil, the animated film is a producing artifact of a cultural pedagogy to teach ways of being and thinking the “worldcystem” capitalistic - colonial - patriarchal, especially with the late scenery of a fascist neoconservative escalation at political and social territories of the country. Anchored in post-structuralist theorizations and in descolonial and (trans)feminist pluriepistemic benchmark, we have analyzed the animated film, highlighting as a “pirate pedagogy” can shake the normative codes of production of knowledge, speeches and practices imposed to bodies, also performing a different genealogy for the sexualities and genders of people from the (de)construction of a “new” physical body, but also epistemological, from Laerte.
CORPOS CAMBIANTES EM “A CIDADE DOS PIRATAS”: É POSSÍVEL UMA PEDAGOGIA “LAERTE” PARA ABALAR AS COLONIALIDADES E OS FASCISMOS IMPOSTOS AOS GÊNEROS?
Keywords: Coloniality; Feminism; Sexualities; Transvestilities